Frobenius 2009. Animal Husbands, Magic Horns and Water Spirits - Reinhardt, Thomas (AAeO - Afrikanistik-Aegyptologie-Online, 2010)
Leo Frobenius 2009. Animal Husbands, Magic Horns and Water Spirits. Folktales From Southern Africa. (Studien zur Kulturkunde Bd. 126), edited, revised and annotated by Sabine Dinslage. With the assistance of Verena Lebéus. 3 Bde., zus. 1283 S., 1. Teilband S. 1-442, 2. Teilband S. 443-926, 3. Teilband S. 927-1283, 7 s/w-Fotos, 2 Faksimile-Reproduktionen, 1 Karte. Köln: Rüdiger Köppe Verlag, € 148, ISBN 978-3-89645-221-4
Keywords: Folktales; Frobenius; Legenden; Märchen